Analysis of the Efficiency and Supply Chain Performance of Copra Using the FSCN Method and Sales Margin - I Gede Rendi Septian Parwanto; Fatlina Zainuddin; Suryadi Hadi; Kadek Agus Dwiwijaya (SAFE-Network, 2026)
This study aims to analyze the performance and efficiency of the copra supply chain in Ongka Malino Subdistrict, Parigi Moutong Regency. The analysis method used is the Food Supply Chain Network (FSCN) approach to examine the supply chain structure as well as the flow of products, information, and finances, combined with a marketing efficiency analysis through the calculation of marketing margins, farmers’ share, and the profit-to-cost ratio. The results identified three marketing channels: Channel I (Farmer → Collector → Wholesaler → Distributor), Channel II (Farmer → Wholesaler → Distributor), and Channel III (Farmer → Distributor). The findings indicate that Channel III is the most efficient channel, with the highest farmer’s share of 66.67% and the lowest total marketing margin of Rp6,000.00/kg. Conversely, Channel I has a farmer’s share of 44.44%, which falls below the 50% efficiency standard, making it less efficient due to the length of the distribution chain. Although in Channel III farmers bear independent transportation costs of Rp800.00/kg, they still earn the highest profit of Rp9,500.00/kg. Simplifying the supply chain has proven to increase farmers’ income and economic efficiency.